Effectiveness of non-invasive brain stimulation in improving sleep quality in insomnia: a systematic review - Mohammad Khosravi; Reza Khosravi (Sleep Science and Practice)
Abstract Introduction Insomnia, a prevalent sleep disorder, significantly impairs cognitive, emotional, and physical health, affecting millions worldwide. Traditional treatments, such as pharmacotherapy, often have limited efficiency and pose risks of dependency and adverse effects. Non-invasive brain stimulation (NIBS), including rTMS, tDCS, and tACS, shows promise in improving sleep quality. This systematic review evaluates the effectiveness and safety of NIBS in treating insomnia. Methods We systematically searched PubMed, Web of Science, and Scopus for studies published from inception to December 2024. A total of 43 studies were included after rigorous screening, featuring diverse designs, sample sizes, and outcome measures. Data were extracted and assessed using the Joanna Briggs Institute (JBI) critical appraisal tool for experimental and quasi-experimental studies. Results rTMS showed the strongest evidence, with most of studies reporting significant improvements in sleep parameters. High-frequency rTMS targeting the dlPFC improved sleep and mood. Also, other cortical areas targeted included the posterior parietal cortex, angular gyrus, and primary motor cortex can also enhance sleep quality, particularly in patients with comorbid insomnia and other psychiatric disorders. tDCS and tACS demonstrated potential, with tDCS enhancing deep sleep and tACS improving sleep onset through neural entrainment. NIBS was safe and well-tolerated. Conclusion NIBS techniques represent a safe and effective non-pharmacological approach to improving sleep quality in insomnia patients. While rTMS has demonstrated strong efficiency, the potential of tDCS and tACS warrants further investigation. Future research should focus on protocol standardization, long-term effects, and personalized interventions.